An experimental study on gas production from fracture-filled hydrate by CO2 and CO2/N2 replacement. (1st June 2018) - Li, Bing; Xu, Tianfu; Zhang, Guobiao; Guo, Wei; Liu, Huanan; Wang, Qiuwen; Qu, Lili; Sun, Youhong
Highlights: The thin layer of hydrate can be formed with ice layer by increasing its temperature. The morphology of MH has an impact on gas production from MH by gas replacement. CO2, CO2 /N2 (3:1) and CO2 /N2 (1:3) were selected for gas replacement. The gas composition and pressure affected the replacement result together. The ice around MH might inhibit the further decomposition of MH and gas replacement. Abstract: The fracture-filled gas hydrate commonly occurs in marine fine-grained sediments and the fracture of rock in permafrost regions. Gas production from fracture-filled methane hydrate by the CO2 replacement method has been investigated. The reservoir condition of permafrost-associated gas hydrate in Muri Basin, Qilian Mountains was taken as an example to set up the experimental parameters. CO2, CO2 /N2 (3:1) and CO2 /N2 (1:3) were selected for gas replacement. Based on the results from six sets of laboratory experiments, we can learn that the factors affecting gas replacement included gas composition for replacement, pressure and the morphology of the hydrate. When the pressure was lower than the equilibrium pressure of CO2 /N2 binary hydrate and the equilibrium pressure of methane hydrate, there was a rapid decomposition process of methane hydrate and might be a transient water freezing process at the first few minutes. The ice around methane hydrate might inhibit the further decomposition of methane hydrate. A higher replacement rate and accumulative methane recovery ratio can be obtained when the morphology of methane hydrate was well distributed thin layer, which could be obtained with the ice layer by gradually increasing its temperature. The thin layer of hydrate is the main morphology of the fracture-filled gas hydrate found in the Qilian Mountain permafrost. Therefore, the gas production from hydrate by CO2 /N2 (3:1) replacement might be a good choice for gas production from hydrate in Muri Basin, Qilian Mountain.